TAXONOMIC STUDIES ON INDIAN GELECHIIDAE VI. A NEW SPECIES UNDER GENUS DIASTALTICA WALSINGHAM FROM NORTH INDIA (LEPIDOPTERA : GELECHIOIDEA) - WALIA, V.K.; WADHAWAN, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
First representative species of genus Diastaltica Walsingham from India i.e. asymmetria sp. nov. is described in detail. The belongingness of this new species collected from Kalesar, Subathu and Sairighat to the Central American genus has been discussed.